MODEL PEMBELAJARAN KOOPERATIF TIPE TUTORSEBAYADALAM PEMBELAJARAN BERBICARA BAHASA JEPANG (PenelitianEksperimenterhadapSiswaKelas X IPA 1 SMA Pasundan 3 Bandung TahunAjaran 2017/2018) - Sri Maryanah, - (2018)
PenelitianinidilatarbelakangiolehadanyakemampuanberbicarabahasaJepangsiswa yang belummemuaskandikarenakanmetodepembelajaranyang kuranginovatif. Terkaithaltersebut, model pembelajarankooperatiftipe tutor sebayabisamenjadisalahsatualternatifdalampembelajaranberbicarabahasaJepang yang diharapkandapatmemberikaninovasibarudalampembelajaran, sertamenciptakansuasanapembelajaranaktifdanmenyenangkansehinggakemampuanberbicarabahasaJepangsiswadapatmeningkat. Tujuanpenelitianadalahuntukmengetahuiefektivitas model pembelajarankooperatiftipe tutor sebayadalampembelajaranberbicarabahasaJepangsiswa SMA Pasundan 3 Bandung.Metode yang digunakandalampenelitianiniadalaheksperimenmurni (true experiment).Berdasarkanhasilanalisis data, diketahuibahwa model pembelajarankooperatiftipe tutor sebayaefektifdigunakandalampembelajaranberbicarabahasaJepang.;---research is motivated by the obstacles faced in learning to speak Japanese, especially the lack of teachers' innovative methods of learning so that learning to speak Japanese becomes boring. Related to that, cooperative learning model of peer tutor can be one of the alternatives in learning to speak Japanese which is expected to give new innovation in learning, as well as create an active and enjoyable learning atmosphere so that the students' ability to speak Japanese can increase. The purpose of this study is to know students' ability to speak Japanese before and after the application of peer tutor learning model and to find outthe effectiveness of the model towards speaking Japanese learning. The method used in this research is quasi experiment "one group pretest-posttest design" with test instrument. The data source is the students of SMA Pasundan 3 Bandung class X IPA 1, 2nd semester, academic year 2017/2018. Based on data processing, it is known that there are significant differences in students' ability to speak Japanese before and after the implementation of cooperative learning model of peer tutor and the use of this learning model is effectively used in learning to speak Japanese;---本研究の問題は不革新な学習方法を実施されたので、日本語学者の話す能力があまり良くないという。この問題に応じて、日本語話す能力を高めるようにアクティブな学習又は面白い学習を実施するのが必要であり、従来の学習方法の代わりピア・ラーニングの協同学習モデルが研究に取り上げる。本研究の目的はSma 3 Pasundan　Bandungの高校生の日本語の会話におけるピア・ラーニングの協同学習モデルの効果を知りたいためである。本研究の研究方法は[True Experiment]方法である。本研究の結果により、ピア・ラーニングの協同学習モデルを実施された結果は効果があるというデータを得られる。